Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Ibu Nifas Tentang Tanda Bahaya Masa Nifas Di TPMB Rosita Medika Babelan Tahun 2023 - Rengganis, Kinta; Siregar, Rohani (NHM PRESS, 2024)
In Indonesia, the number of maternal deaths compiled from family health program records at the Ministry of Health in 2020 showed 4,627 deaths. This figure has increased compared to 2019 which recorded 4,221 deaths. Based on causes, the majority of maternal deaths in 2020 were caused by bleeding with 1,330 cases, hypertension in pregnancy with 1,110 cases, and circulatory system disorders with 230 cases. The purpose of this study is to determine the factors related to postpartum mothers' knowledge about the danger signs of the postpartum period at TPMB Rosita Medika Babelan in 2023. This research method uses the chi-square test, using a cross sectional method. The population in this study was 50 respondents with a sample size of 50 postpartum mothers. The sampling technique in this research used a total sampling technique. The instrument in this research used a questionnaire and was analyzed using univariate analysis and bivariate analysis. The results of the research show that variables related to postpartum mothers' knowledge about the danger signs of the postpartum period are age with a p value of 0.045 and an OR value of 8.33, parity with a p value = 0.044 and an OR value = 3.800, and support from health workers with a p value = 0.045 and OR value 8.3. Meanwhile, the variable that is not related is education with p value = 0.132 and OR value 4.000 The conclusion of this research is that there is a relationship between age, parity, and support from health workers and danger signs during the postpartum period. Meanwhile, in education, there is no relationship between the danger signs during the postpartum period and the danger signs during the postpartum period at TPMB Rosita Medika Babelan Advice for the community, especially postpartum mothers, to better understand the danger signs during the postpartum (postpartum) period.